(untitled) (Bangladesh Veterinarian, 2012)
Chromosomal aberrations or abnormal karyotypes could be one reason for reproductive failure in breeding bulls. The objective of the study was to detect chromosomal abnormalities and their relation with fertility problem in cattle and water buffalo breeding bulls. Blood samples were collected from 30 buffalo bulls and 23 Holstein or Holstein-Friesian cross bred bulls for lymphocyte culture. No gross chromosomal abnormality was detected. However, a few samples exhibited polyploidy, premature centromeric division, chromosomal fragmentation, aneuploid cells, fragile site, chromatid gaps or breaks. These aberrations were not consistent feature in a particular animal; therefore, the aberrations may not have obvious effects on fertility. However, such aberrations should be scored in regular screening as a high percentage of such abnormalities can be associated with reduced fertility. DOI: http://dx.doi.org/10.3329/bvet.v29i1.11885 Bangl. vet. 2012. Vol. 29, No. 1, 17-21